Effects of communication, trust, and respect on shared decision-making: insights from healthcare providers in Chinese public hospitals - Chen, Lu; Chu, Huijun; Wang, Hui; Du, Liang; Gao, Yumeng; Shen, Jie (Frontiers in Medicine, 2025)
BackgroundShared decision making (SDM) could significantly enhance health knowledge, treatment adherence, and doctor-patient relationship, but multifaceted barriers have influenced the implementation of SDM worldwide. There are now few studies on SDM process from the perspective of healthcare workers who often act as the initiators of SDM. Focusing on healthcare providers, this study aimed to explore the mechanism by which provider-patient communication, trust, and respect influenced SDM within the context of China’s three-tier public hospital system.MethodsA stratified sampling was employed to survey doctors and nurses from public hospitals in Shanghai, China. The questionnaire included respect, patient-provider communication, trust, SDM, and socio-demographic information. Structural equation modeling was used to examine the study hypotheses, after controlling demographics covariates.ResultsThere were 778 participants included in this study. The constructs in our study exhibited good reliability and validity, and the SEM demonstrated good fit (CFI = 0.978, TLI = 0.974, RMSEA = 0. 039, SRMR = 0.036). Provider-patient communication and trust were significant factors influencing SDM (p < 0.001), and R-square for regression models were all more than 30%. Additionally, trust between providers and patients mediated the relationship between communication and SDM (effect = 0.221, 95% CI: 0.133–0.359), and the mediating effect accounted for 39.89% of the total effect in primary hospitals, while it was 20 and 19.34% in secondary and tertiary hospitals. Moderating analysis showed that respect positively influences the relationship between communication and SDM in secondary hospitals (effect = 0.327, 95% CI: 0.156–0.498), but this effect was not significant in primary (95% CI: −0.035-0.405) or tertiary hospitals (95% CI: −0.072-0.210).ConclusionProvider-patient communication and trust were important factors influencing SDM according to healthcare providers, and respectful behaviors was key to improving communication and SDM in the secondary hospital. These suggested evidence for the development of strategies to promote SDM in the future.